Kinematic Analysis of the Ushiro Mawashi Geri Kick in Karate Athletes - Efrida Eriani Hasibuan; Rahma Dewi; Indra Kasih; Amir Supriadi (Gladi : Jurnal Ilmu Keolahragaan, 2026)
This study aimed to analyze the kinematic characteristics of the Ushiro Mawashi Geri kick performed by karate athletes using Dartfish motion analysis software. The study employed a qualitative descriptive approach involving five male karate athletes selected through purposive sampling based on specific criteria. Data were collected through observation, video documentation, kicking performance tests, and motion analysis using Dartfish software. The analysis focused on the preparation, execution, and follow-through phases of the kick. The findings showed that the athletes generally demonstrated good performance in executing the Ushiro Mawashi Geri technique. The Dartfish analysis results indicated 3.33% in the excellent category, 73.67% in the good category, 13.00% in the poor category, and 10.00% in the very poor category. Several technical weaknesses were still identified, particularly in body balance, movement coordination, and foot positioning during the rotational and follow-through phases. This study concludes that kinematic analysis using Dartfish software can be utilized as an evaluation tool to improve the effectiveness and efficiency of Ushiro Mawashi Geri techniques in karate training. However, due to the limited number of participants, the findings are exploratory and cannot be generalized broadly.